Development of Telemetry System for Light Intensity Measurement by Using a Wireless LAN - I Nyoman Sudiana (Universitas Halu Oleo, 2014)
A remote measuring system using wireless LAN (Local Area Network) for light intensity measurement has been developed. It made use of a socket programming and TCP/IP protocol. The system consisted of a light source, an OPT 101 sensor, an ADC 0804, an AT89C51 microcontroller, and a wireless LAN system. The result of sensor calibrations showed a linear relationship between light intensity and sensor output (I = 5.6337 V- 4.4912; R2 = 0.9913). The light intensity varied from 51 to 3,912 lux. By using Delphi and assembler utility for microcontroller, the system could be automated and displayed in a form of light intensity values both on the server and client computers. In order to see the influence of the server and client computer distance receptivity on the measurement result, the signal strength was also measured by using Net Stumbler software whose distances were varied from 2 to 226 m.